The effectiveness of hedge fund investment strategies under various market conditions - Michał Falkowski; Agata Sierpińska-Sawicz; Piotr Szczepankowski (Contemporary Economics, 2020)
The main purpose of the article was to analyze the effectiveness of the basic investment strategies used by hedge funds in the long term (years 1994-2015) and during the global financial crisis (years 2007-2009). Using information from commercial databases we attempted to verify the hypothesis that alternative hedge funds, regardless of the type of strategy they use, are capable of achieving better outcomes than other capital allocation options, at any time and under a variety of market conditions. We analyzed hedge funds effectiveness in two stages. For stage one, we performed a profitability analysis for the whole hedge funds sector in the two periods and compared the results with the stock rates of return achieved by investors in the global market for the same period and with the risk-free rate. At stage two we calculated ratios that included rate of return and risk, though only for specific strategies. We used traditional portfolio performance measures (Sharpe, Treynor, Jensen ratios) as well as the newer ones (the Sortino ratio, downside deviation). The results show no confirmation that investments carried out by hedge funds are more risky than traditional capital investment methods. Risk associated with investments by the analyzed entities was lower not only in times of prosperity, but also during crisis, providing a clear indication of the higher effectiveness of entities operating in the alternative investment sector and regardless of the changes taking place in the financial market, the length of the capital investment period or the investment strategy being pursued.
Keywords: G01; G20; G23; G32; 330; hedge funds; efficiency; investment strategies; financial crisis